PRILAKU MAHASISWA DALAM MEMILIH TEMPAT KOST DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Lestari, Dewi; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the new of Kelurahan Simpang BaruKecamatan Tampan Kota pekanbaru in the place of boarding Srikandi, PondokanIlham, Tri Putra. The purpose of this study is to determine the behavior of studentsin choosing a boarding palace and to find out the social interactiaon betweenstudent boarding residents in the new of Kelurahan Simpang Baru KecamatanTampan Kota pekanbaru. This study was conducted on 50 respondents found in 3boarding places that have been set by researchers who are determined based onnon probability sampling using quota sampling. Research instruments usingobservasi, koesioner, and documentation techniques and uses media spss 20.Research conducted found that in choosing a student boarding house tends tochoose a complete boarding facilities both public facilities and room facilitiesprovided by the owner of boarding, comfort, sucurity, freedom, image good,distance access and based on parental income. Forms of student social relationsbetween boarders, where students with co hosts there are activities in the form ofsharing food, borrowing borrow money with fellow students boarding board,mutual learning together or study groups with co horst. In this study students withfellow boardes more connect relationships because many students who conductactivities that lead to a positive relationship. This study does not see any conflict oractivity that leads to dissociative activities because based on research conductedby the research that student s with hosts did not conduct activities that lead tonegative things.Keywords : Rational Choice, Social Interaction